Political Marketing Strategy for the Incumbent Candidate Pair in the 2020 Asahan District Elections - Jimmy Hendrik; Muryanto Amin; Warjio (PERSPEKTIF, 2023)
This study aims to analyse the political marketing strategy undertaken by a pair of rural candidates (Surya-Taufik) in the face of a simultaneous general election of the head of the area (Electors) in 2020 in Kabupaten Asahan. There are a couple of farmers in the district's electoral campaign that are often regarded as strong candidates, which is because they are considered to have more dominant political capital such as popularity capital, networks and images. A pair of evaluated maps have a good image as a popular official in the public eye, but if supported by positive performance figures will certainly strengthen the relationship between the voters and the candidate pair in terms of winning. The theory used to explain these problems is democracy theory, political market theory, political communication theory and role theory. Based on the results of field research, it can be concluded that the process of winning a candidate pair (Surya-Taufik) is a candidate process, forming a winning team, doing research, designing political products, implementing political products, conducting political communication and building commitment. The political marketing theory of the candidate pair (Surya-Taufik) also uses three approaches: push marketing, pull marketing and pass marketing in conducting political campaigns. The strategy is a comprehensive step taken by the candidate pair (Surya-Taufik) and the successful team that can be accepted by all communities.